Recent Advances in Entomological Research From Molecular Biology to Pest Management - Liu, Tongxian; Kang, Le.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
In recent years the field of entomology, due in part to the penetration of other disciplines, has made rapid progress. (3z(BRecent Advances in Entomological Research: From Molecular Biology to Pest Management(3y (Bincludes 25 chapters contributed by more than 40 distinguished entomologists and introduces the latest progress in entomology, from molecular biology, insect-plant interactions and insecticide toxicology, to emerging technologies in pest management. Not only is the book interesting and informative, but it provides useful, innovative research advances and will serve as a valuable resource for entomologists, zoologists, botanists and other researchers in the field of plant protection. Tong-Xian Liu is a professor of entomology at the College of Plant Protection, Northwest A&F University, China. Le Kang is a professor of entomology at the Institute of Zoology, Chinese Academy of Sciences, China.s
Insect-Plant Interactions -- Molecular Biology, Physiology, Biology, Behavior and Ecology -- Insect Toxicology and Insecticide Resistance Management -- Emerging Pest Management Strategies and Technologies.
Keywords: Life sciences; Agriculture; Ecology; Plant breeding; Entomology; Life Sciences; Entomology; Plant Breeding/Biotechnology.; Ecology; Agriculture